Effect of Feeding Pomegranate and Rohitaka on Rumen Fermentation Parameters in Male Buffalo Calves - Singh, Iqbal; Hundal, Jaspal Singh; Singh, Gurpreet; Wadhwa, Manju; Lamba, Jaspal Singh (Indian Journal of Animal Nutrition, 2018)
To study the effect of herb supplementation, 6 fistulated animals were selected and divided randomly into 2 groups of 3 each. All the animals were offered conventional diet with roughage to concentrate ratio of 65:35 on DM basis as TMR with or without Pomegranate (Anar chal) or Rohitaka @ 2% of DMI. After 15 days adaptation period, rumen liquor was collected at 0, 2, 4, 6, 8, 12hr post feeding for three days, pooled and analyzed for various parameters. The study revealed that Anar chal had significantly higher (p<0.001) concentration of total phenols, true tannins and methanol soluble saponins whereas Rohitaka was rich in vitamin C, flavonoids (p<0.001) and water soluble saponins. The total nitrogen in rumen liquor was significantly (p<0.001) higher in Anar chal (0.32mg/dl) or Rohitaka (0.37 mg/dl) supplemented group as compared to control diet (0.18 mg/dl). The true nitrogen and ammonical-N levels were also higher (p<0.001) in rumen liquor of animals fed Anar chal (82.9% & 41.4%) and Rohitaka (122.3% & 46.3%) in comparison to rumen liquor of control group. Supplementation of herbs increased (p<0.01) the production of TVFAs and individual fatty acids in comparison to control. The acetate to propionate ration varied (p<0.01) from 3.35 (Anar chal supplemented diet) to 3.06 (control diet). Total bacterial count was significantly higher (p<0.001) in the rumen of animals fed diet supplemented with Anar chal (18.52×109) or Rohitaka (22.62×109) as compared to control (12.75×109) diet fed group. Total protozoa count was significantly (p<0.05) lower postprandial in Anar chal (1.0×105) supplemented diet in comparison to control (1.75×105) or Rohitaka (3.23×105) supplemented diet. The percent holotrichs were significantly (P<0.001) increased, whereas that of entodinomorphs were significantly (P<0.001) reduced on herb supplementation. It was concluded that supplementation of Anar chal or Rohitaka @ 2% of DMI resulted in improved rumen biochemical profile, VFA production and microbial population, however, Rohitaka had an edge over Anar chal in improving rumen parameters.